2019
DOI: 10.17341/gazimmfd.479086
|View full text |Cite
|
Sign up to set email alerts
|

Evrişimsel sinir ağı ve iki-boyutlu karmaşık gabor dönüşümü kullanılarak hiperspektral görüntü sınıflandırma

Abstract: Highlights:Graphical/Tabular Abstract  Deep-learned and Gabor filtering-based feature fusion approach is proposed.  A seven layer deep convolutional network is designed to learn deep features.  Classification performance of the proposed hybrid method is comprehensively evaluated.In this paper, a new hyperspectral image classification method based on 2-dimensional complex Gabor filtering and deep convolutional neural network is proposed. To extract a set of features at multiple orientations and frequencies, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Moreover, combined with the classifcation advantages of the CNN [51,52], a fusion network for image classifcation can be constructed based on an SAE optimization, improving classifcation performance compared to traditional data processing [53,54]. Te semisupervised classifcation algorithm based on multilabeled samples and deep learning [55], with labels from both the nearest domain information and training samples [56,57], and nonlabeled samples obtained from self-teaching learning, yields an efective semisupervised hyperspectral image classifcation method [58,59]. Numerous classifcation experiments based on deep learning algorithms on a variety of hyperspectral data found that deep learning algorithms are the optimal classifcation algorithms in most cases [60][61][62][63][64][65][66].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, combined with the classifcation advantages of the CNN [51,52], a fusion network for image classifcation can be constructed based on an SAE optimization, improving classifcation performance compared to traditional data processing [53,54]. Te semisupervised classifcation algorithm based on multilabeled samples and deep learning [55], with labels from both the nearest domain information and training samples [56,57], and nonlabeled samples obtained from self-teaching learning, yields an efective semisupervised hyperspectral image classifcation method [58,59]. Numerous classifcation experiments based on deep learning algorithms on a variety of hyperspectral data found that deep learning algorithms are the optimal classifcation algorithms in most cases [60][61][62][63][64][65][66].…”
Section: Introductionmentioning
confidence: 99%